2017
DOI: 10.3389/fmicb.2017.02040
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Aspergillus fumigatus DNA Is Quantitatively Correlated to Galactomannan in Serum

Abstract: The performance of antigen galactomannan (GM) for diagnosing invasive aspergillosis (IA) is hampered by the occurrence of false-positive results. Quantitative PCR has been proposed to improve the diagnosis of IA. Therefore, we analyzed the value of performing a PCR test to the GM-positive serum sample. Using a quantitative PCR assay specific for Aspergillus fumigatus 28S ribosomal DNA, we retrospectively tested 422 GM-positive (Platelia Bio-Rad kit) serum samples collected over 1 year from 147 patients. The ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…Although efforts were undertaken to standardize PCR protocols to be used for the detection of Aspergillus DNA in blood samples, the use of PCR remains controversial and has not been included in the consensus IA definitions of the EORTC. Comparisons of PCR with antigen detection have been repeatedly undertaken (142). Meta-analyses have shown that the specificity of both GM and ␤1,3 glucan tests was significantly higher than that of PCR in serum samples.…”
Section: Figmentioning
confidence: 99%
“…Although efforts were undertaken to standardize PCR protocols to be used for the detection of Aspergillus DNA in blood samples, the use of PCR remains controversial and has not been included in the consensus IA definitions of the EORTC. Comparisons of PCR with antigen detection have been repeatedly undertaken (142). Meta-analyses have shown that the specificity of both GM and ␤1,3 glucan tests was significantly higher than that of PCR in serum samples.…”
Section: Figmentioning
confidence: 99%
“…Putative IPA was considered if one of the following conditions was met, i.e. 1-presence of Aspergillus fumigatus in culture; 2-BAL galactomannan index >0.8 AND beta-D-glucan >80 pg/mL; 3- Aspergillus fumigatus qPCR with quantification cycle <35 in pulmonary specimens; 7 and/or 4-serum beta-D-glucan >80pg/mL AND serum galactomannan index >0.5. Of note, direct examination of respiratory specimens was not performed to avoid operator contamination.…”
mentioning
confidence: 99%
“…This may be due to reporting of a lesser time to mortality (ϳ1 month), whereas in most of the studies time to mortality is Ն3 months. Poor prognosis has been previously correlated with varied mycological diagnostic criteria, including culture, galactomannan antigen (GM), and PCR positivity (43)(44)(45)(46)(47). It has been associated with persistent higher GM values, and it was recently found to be linked with higher PCR fungal load (47).…”
mentioning
confidence: 99%